Strategi Komunikasi Pemasaran dalam Membangun Brand Image Lembaga Sertifikasi Profesi Manajemen Risiko - Adlina, Bernadette Tiur; Loisa, Riris (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Professional Certification Institute (LSP) is an institution that carries out activities in the field of professional competence, and has received permission from the National Professional Certification Agency (BNSP). This professional certification is given by organizations or institutions that are competent and have understood their expertise in a particular field. BNSP noted that the number of labor certifications experienced a significant decline from 2006 to 2021. New problems in the world of work emerged, because professional certification is one of the benchmarks to help one's career path in the world of work. In retaining clients, a company must have the right marketing communication strategy in carrying out the tasks requested by the client. This research has the aim of getting an overview of the branding built by the company and an overview of the company's marketing communication strategy. The concept of this research is corporate communication strategy, advertising, public relations and publicity, personal selling, direct marketing, strength, uniqueness, and excellence. This research approach is qualitative with case study methodology. Sources of data used as a reference is a variety of primary data consisting of interviews and observations. The research subjects are LSPMR employees and the research object is the Risk Management Professional Certification Institute (LSPMR). The results of the study show that the overall marketing strategy carried out by LSPMR is direct marketing and personal selling. Lembaga Sertifikasi Profesi (LSP) merupakan lembaga yang melaksanakan kegiatan di bidang kompetensi profesional, dan telah mendapat izin dari Badan Nasional Sertifikasi Profesi (BNSP). Sertifikasi profesi ini, diberikan oleh organisasi atau lembaga-lembaga yangberkompeten dan telah memahami keahliannya di bidang tertentu. BNSP mencatat, jumlah sertifikasi tenaga kerja mengalami penurunan yang signifikan dari tahun 2006 sampai tahun 2021. Permasalahan baru di dunia kerja muncul, karena sertifikasi profesi ini salah satu tolok ukur untuk membantu jenjang karir seseorang di dunia kerja. Dalam mempertahankan klien, sebuah perusahaan harus memiliki strategi komunikasi pemasaran yang tepat dalam menjalankan tugas yang diminta oleh klien. Penelitian ini memiliki tujuan mendapatkan gambaran branding yang dibangun perusahaan dan gambaran strategi komunikasi pemasaran pada perusahaan. Konsep penelitian ini adalah strategi komunikasi perusahaan, periklanan, hubungan masyarakat dan publisitas, penjualan personal, pemasaran langsung, kekuatan, keunikan, serta keunggulan. Pendekatan penelitian ini adalah kualitatif dengan metodologistudi kasus. Sumber data yang dijadikan acuan adalah berbagai data primer yang terdiri dari wawancara dan observasi. Subyek penelitiannya adalah karyawan LSPMR dan objekpenelitiannya adalah Lembaga Sertifikasi Profesi Manajemen Risiko (LSPMR). Hasil dari penelitian memperlihatkan bahwa keseluruhan strategi pemasaran yang dilakukan oleh LSPMR adalah pemasaran langsung serta penjualan personal.